The impact of PhD studies on mental health: A longitudinal population study - Sanna Bergvall; Clara Fernström; Eva Ranehill; Anna Sandberg (Lund University, School of Economics and Management, Department of Economics, 2024)
Recent self-reported and cross-sectional survey evidence documents high levels of mental health problems among PhD students. We study the impact of PhD studies on mental health care uptake using Swedish administrative records of prescriptions for psychiatric medication for the full population of PhD students. First, we provide descriptive evidence that PhD students collect psychiatric medication at a higher rate than a matched sample of individuals holding a master's degree, but at a lower rate than a matched sample from the general population. Second, we implement an event study analysis and document that, in the years preceding their PhD studies, prospective students collect psychiatric medication at a rate similar to that of a matched sample of individuals holding a master's degree. However, following the start of PhD studies, the use of psychiatric medication among PhD students increasessubstantially. This upward trend continues throughout the course of PhD studies, with estimates showing a 40 percent increase by the fifth year compared to pre-PhD levels. After the fifth year, which represents the average duration of PhD studies in our sample, we observe a notable decrease in the utilization of psychiatric medication.
Keywords: I10; I23; 330; Mental health; PhD studies; psychiatric medication